Environmental aspects of rational use and protection of lands - Bavrovska, N. (Land Management, Cadastre and Land Monitoring, 2023)
The current state of land use in Ukraine is characterized by high agricultural development and a high percentage of plowed land (more than 56%). As of 2022, the state of Ukraine’s land resources could be described as cause for concern, as there has been a violation of the ecologically balanced ratio between land categories, a decrease in the area of unique steppe areas, excessive plowing of the area and violation of the natural process of soil formation. Protection and rational use of land is one of the most important tasks of society in the process of using natural resources, since food supplies obtained from the use of land make up 98 percent. The article presents an analysis of the main ecological problems of land use that have arisen as a result of the full-scale war in Ukraine. The need to solve the problems of rational land use due to the cross-cutting nature of environmental policy and the development of the country based on the European Green Course, taking into account the environmental standards at all levels of policy formation and implementation in the field of environmental protection and rational nature use, through the development and implementation of land management schemes and technical and economic justifications, is substantiated use and protection of lands of administrative-territorial units, territories of communities; automated platforms, information and analytical systems and remote sensing of the Earth; criteria and technologies for monitoring land and land relations, including artificial intelligence algorithms.